Studi Waktu Penyambungan terhadap Keberhasilan Sambung Pucuk pada Wani Ngumpen Bali (Mangifera caesia Jack. Var. Ngumpen Bali) - I GUSTI MADE KUSUMA ARDANA; NI LUH MADE PRADNYAWATHI; HESTIN YUSWANTI (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2022)
Study of Grafting Time on the Success of Grafting on Wani Ngumpen Bali (Mangifera caesia Jack. Var. Ngumpen Bali) Wani ngumpen Bali is a mango relative plant that grows in Bali and potential to be widely developed because it has unique and superior properties because 90% of the fruit produced has small seeds and thick flesh that makes it seem like it has no seeds. Considering the wani ngumpen Bali plant is difficult to propagate through generative because the seeds are relatively difficult to get so that propagation is done using vegetative cultivation technology. One of the vegetative propagation is grafting or connecting shoots. This research aims to study the timing of splicing to the success rate of wani ngumpen Bali shoots. The study was conducted from February to April 2021. This study was conducted in Sudaji Village, Sawan Subdistrict, Buleleng Regency, with an average height of 500 mdpl, rainfall of 3000 mm per year with a temperature of 18o-23 o C.This study used a randomized block design (RBD) with 1 factor consisting of 5 levels treatment time grafting. The treatment was repeated 7 times and in each replication there were 2 plants, so that there were 70 experimental units, with treatment W1 (at 09.00-10.00 am), W2 (at 11.00-12.00 pm), W3 (at 13.00-14.00 pm), W4 (at 15.00-16.00 pm), W5 (at 17.00-18.00 pm). The data obtained were analyzed descriptively because the research data did not meet the requirements for statistical tests. In the nursery, shoots of wani var. Ngumpen Bali is affected by the connection time. The success of shoot grafting in wani ngumpen Bali, best during the day, at 13.00-14.00, with percentage of seedlings successfully growing 35,51%, shoot length 21.10 cm and number of leaves 13 strands.